Ghanaian Screendance Perspectives: The Nuance of ‘Sankofaism’ as Emerging Aesthetics and Rejection of Orthodoxy - Benagr, Samuel; Ofosu, Terry B.K. (The International Journal of Screendance, 2016)
Screendance is a hybrid art in which choreographic and film techniques are necessary for creating texts where the body dialogues with camera. Ghanaian dance film is best understood within the context of postmodern discourse. This article argues that indigenous and foreign cultural practices are convoluted by morality and hegemonic influence of western culture. Moving from orthodoxy, the Ghanaian dance film re-contextualizes dance practice and film techniques into a composite construct with a tinge of Afrocentrism. Framed by *critical sankofaism*, screendances in Ghana are discussed as being influenced by individual musician's ideas with western biases. Dances for television are shaped by institutional guidelines gleaned from Ghanaian culture. Using *Heyba* and screendance at TV3 Network and GTV, this article discusses dance films as an emerging aesthetic that re-interprets the function of bodies, their relationships with the camera, and concludes that more than being a hybrid site, screendance in Ghana is a 'polybrid'.